Extravasation Injuries, Pressure Ulcers and Ocular Surface Disorders in a Tertiary Paediatric Intensive Care Unit in South India - Amatya, Puja; Sadasivam, Kalaimaran (Journal of Nepal Paediatric Society, 2020)
Introduction: Extravasation injuries, pressure ulcers (PU), and ocular surface disorders (OSD) like exposure keratitis are common problems that we encounter in critically ill children admitted in Paediatric Intensive Care unit (PICU). There is sparse data regarding these injuries due to under reporting by staffs in intensive care unit. The primary aim of this study was to know the prevalence of extravasation injuries, ocular surface disorders and pressure ulcers in tertiary intensive care unit of south India. The secondary objective of this study was to re-evaluate the prevalence of these injuries after interventions. Methods: During pre-intervention period, number of children with extravasation injuries, pressure ulcers and ocular surface disorders were identified. The qualitative improvement practices was implemented to decrease the prevalence of these injuries. This was followed by re-evaluation of these injuries during post-intervention period. Results: During pre-intervention period the overall prevalence of these injuries was 36/273 (13.2%). The prevalence of extravasation injuries, pressure ulcers and ocular surface disorders was 16/273 (5.9%), 12/273 (4.4%) and 8/273 (2.9%) respectively. The qualitative improvement practices were implemented in intensive care unit. During post-intervention period, the prevalence of these injuries was reduced to 10/157 (6.4%). The extravasation injuries reduced to 4/157 (2.5%), PUs to 4/157 (2.5%) and OSD to 2/157 (1.3%). Conclusions: The extravasation injuries, PUs and OSD are common problems in critically ill children. The qualitative improvement practices should be implemented and reinforced in intensive care units to prevent these injuries.